A rational three-step calcination strategy for synthesizing high-quality LiNi0.5Mn0.3Co0.2O2 cathode materials: The key role of suppressing Li2O formation. (20th October 2018) - Gao, Tian-Peng; Wong, Ka Wai; Fung, Ka Y.; Zhang, Wei; Ng, Ka Ming
Abstract: LiNi0.5 Mn0.3 Co0.2 O2 cathode materials synthesized via conventional one-step and two-step calcination strategies suffer from high contents of surface impurities and structural defects (i.e., Ni 2+ /Li + cation mixing and oxygen vacancy), resulting in suboptimal electrochemical performance. In the present study, the formation of Li2 O during calcination is found to be detrimental and responsible for the low quality of LiNi0.5 Mn0.3 Co0.2 O2 . Thus, a three-step calcination strategy is devised to significantly reduce surface impurities and structural defects through strategically suppressing Li2 O formation. The calcination strategy involves first melting of Li precursor, then reaction and conversion of Li precursor with Ni0.5 Mn0.3 Co0.2 (OH)2 to form LiNi0.5 Mn0.3 Co0.2 O2 without Li2 O generation, and finally formation of a layered structure. The as-prepared LiNi0.5 Mn0.3 Co0.2 O2 possesses smooth morphology, much reduced surface impurities, Ni 2+ /Li + cation mixing, and oxygen vacancy. The corresponding Ni 2+ occupancy at Li sites and oxygen vacancy are only 2.2% and 1.7%, respectively. The as-prepared LiNi0.5 Mn0.3 Co0.2 O2 also exhibits high capacity (178.8 mAh g −1 at 0.1 C), good cycle performance (83.4% capacity retention at 100th cycle), and excellent rate capability (97.4 mAh g −1 at 5 C). This calcination strategy is applicable to LiOH·H2 O, LiNO3 and Li2 CO3 as Li precursors. The underlying mechanism of this three-step calcination strategy is elucidated. Graphical abstract: Highlights: Three-step calcination is devised to synthesize high-performance LiNi0.5 Mn0.3 Co0.2 O2 . Surface impurities, Ni 2+ /Li + cation mixing, and oxygen vacancy are reduced by suppressing Li2 O formation during calcination. Typical Li precursors – LiOH·H2 O, LiNO3 and Li2 CO3 – can take advantage of this calcination strategy. The underlying mechanism has been elucidated.